State interventions to rescue banks during the global financial crisis - Abreu, J. F. (2019)
We model unique state interventions to rescue commercial banks during the 2008-09 global financial crisis with the complementary binary logistic model that accommodates their skewed distribution. Our findings show that large and illiquid banks, and banks from countries with weak regulations, and weak shareholder and creditor rights are more likely to receive state interventions. These findings remain robust to a restricted definition of state intervention, alternative measures of bank fundamentals, placebo estimations, counterfactual sampling with propensity scores, bank and country sample splits, and the standard logistic model. These bank and incremental country level predictors can help regulators and supervisors limit future state interventions.